Have the Politics of Rate Regulation Produced a Better No-Fault Regime for Ontario ? - Feldthusen, Bruce (Les Cahiers de droit, 1998)
Ontario has changed its no-fault legislation substantially three times in the past decade. These changes have reflected the interest group lobbying of the insurance industry and the practising bar. However, the main and explicit motivation, especially for the latest revision, has been the government's desire to regulate rates. With the Automobile Insurance Rate Stability Act the government appears to have struck a very successful compromise. The lawyers have been allowed an increased, albeit limited, right to sue in tort. The insurers have achieved more certainty, with stricter time and monetary limits on benefits for non-catastrophic injury. Rates have been reduced in part through lower benefit levels, but primarily by throwing the cost of automobile accidents on to other collateral sources. There is, therefore, some subsidization of driving inherent in the legislation. There are also compensation gaps, especially in long term health care, that affect mainly the most vulnerable members of society. Both these shortcomings could and should be easily corrected. So far, it would appear that the politics of rate regulation have generated an improved no-fault automobile accident compensation scheme for Ontario.